(untitled) - Diệp, Kim Chi (USA, 2011)
This case study explored the perceptions of stakeholders about the development and delivery of information literacy instruction (ILI) to student at four universities, identified perceived challenges of including IL as a credit course in the curiculum, and resulted in a conceptual framework of best practices based on the findings. Constructs from change theory, learning theory, leadership theory and collaboration theory served as lenses to interpret the results
Keywords: Information literacy,Kỹ năng thông tin,Structural frames,Cấu trúc khung chương trình; Study and teaching,Học và giảng dạy